2007
DOI: 10.1016/j.yexcr.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ROCK by RhoA is regulated by cell adhesion, shape, and cytoskeletal tension

Abstract: Adhesion to the extracellular matrix regulates numerous changes in the actin cytoskeleton by regulating the activity of the Rho family of small GTPases. Here, we report that adhesion and the associated changes in cell shape and cytoskeletal tension are all required for GTP-bound RhoA to activate its downstream effector, ROCK. Using an in vitro kinase assay for endogenous ROCK, we found that cells in suspension, attached on substrates coated with low density fibronectin, or on spreading-restrictive micropattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
182
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(204 citation statements)
references
References 31 publications
16
182
1
Order By: Relevance
“…The observed increase in cell spreading ( Fig. 2A,B) fits well with a decrease in actomyosin contractility, because MRLC needs to be downregulated to allow cell spreading, either through the RhoA-ROCK pathway (Arthur and Burridge, 2001;Arthur et al, 2000;Bhadriraju et al, 2007) or through MLCK (Takizawa et al, 2007). Contractility is also required for the positioning of the nucleus during directed cell migration (Gomes et al, 2005), and a decrease concurs with the observed decrease in orientation of the Golgi towards the wound.…”
Section: Escrts Positively Regulate Myosin Light Chain Functions Throsupporting
confidence: 69%
“…The observed increase in cell spreading ( Fig. 2A,B) fits well with a decrease in actomyosin contractility, because MRLC needs to be downregulated to allow cell spreading, either through the RhoA-ROCK pathway (Arthur and Burridge, 2001;Arthur et al, 2000;Bhadriraju et al, 2007) or through MLCK (Takizawa et al, 2007). Contractility is also required for the positioning of the nucleus during directed cell migration (Gomes et al, 2005), and a decrease concurs with the observed decrease in orientation of the Golgi towards the wound.…”
Section: Escrts Positively Regulate Myosin Light Chain Functions Throsupporting
confidence: 69%
“…Cells restrained in their spreading for instance display high RhoA but low ROCK activity (Bhadriraju et al, 2007). This suggests that mechanical properties of the substratum may impinge on RhoA signaling by preventing or restricting binding of the GTPase to a subset of downstream effectors.…”
Section: Discussionmentioning
confidence: 99%
“…Stretch applied on a cell due to external mechanical force or attachment to the stiffer substrates affects actin near the adhesion site and is followed by recruitment of adhesion complex proteins and global cytoskeletal rearrangements (Galbraith et al, 2002;Riveline et al, 2001). Multiple actinbinding proteins at the cell adhesion sites directly respond to substrate rigidity (overviewed in Dobereiner et al, 2005), resulting in changes to all steps of the migration cycle and all of the structural and signaling molecules involved (Beningo et al, 2004;Bhadriraju et al, 2007;Gunzer et al, 2000;Knight et al, 2000).…”
Section: Extracellular Matrix and Force Sensing: Paving The Pathways mentioning
confidence: 99%